1994
DOI: 10.1523/jneurosci.14-01-00068.1994
|View full text |Cite
|
Sign up to set email alerts
|

Memory through metamorphosis in normal and mutant Drosophila

Abstract: To establish that a stable, long-lasting form of memory exists in Drosophila, we trained third-instar larvae by electroshocking them in the presence of a specific odor using a Pavlovian conditioning procedure. We show that conditioned odor avoidance produced in larvae still was present in adults 8 d later. Such memory through metamorphosis was specific to the temporal pairing of odor and shock; presentations of odors alone or shock alone did not produce a change. Thus, the memory involved associative processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
130
1
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(139 citation statements)
references
References 57 publications
7
130
1
1
Order By: Relevance
“…Overall, our data indicate that memory enhancement begins between 1 and 3 h after single cycle training and reverts to normal within 4 days after spaced training. These results are entirely consistent with a model where memory enhancement in DC0 B3 /ϩ and DC0 H2 /ϩ flies consists of a specific increase in ARM (25).…”
Section: Dc0/؉ Mutations Do Not Affect Ltm and Enhance Arm Independentlysupporting
confidence: 90%
See 1 more Smart Citation
“…Overall, our data indicate that memory enhancement begins between 1 and 3 h after single cycle training and reverts to normal within 4 days after spaced training. These results are entirely consistent with a model where memory enhancement in DC0 B3 /ϩ and DC0 H2 /ϩ flies consists of a specific increase in ARM (25).…”
Section: Dc0/؉ Mutations Do Not Affect Ltm and Enhance Arm Independentlysupporting
confidence: 90%
“…Seven hours after a single cycle of training, shorter forms of memory have decayed, leaving ARM as the predominant remaining memory phase (21). The second form of consolidated memory, LTM, forms only after multiple spaced trainings for aversive associations (25).…”
Section: Identification Of Specific Point Mutations That Improve Memorymentioning
confidence: 99%
“…This was further confirmed with another allele, rut 2080 . Similarly, dnc 1 , defective in cAMP phosphodiesterase activity Byers et al, 1981), showed no RI stimulation, confirming the previous results that dnc larvae showed no initial learning (Aceves-Piña and Tully et al, 1994a). Thus, the requirement of both rut and dnc activities strongly argues for the importance of cAMP signaling for larval olfactory learning.…”
Section: Importance Of the Camp Signaling Pathway And Ksupporting
confidence: 84%
“…In addition, whereas the adult brain is formed through complex reorganization during metamorphosis, the larval brain is a simple extension of the embryonic axonal plan (Nassif et al, 2003). However, despite potential advantages, learning and memory studies with the Drosophila larva have been limited (Aceves-Piña and Heisenberg et al, 1985;Tully et al, 1994a;Dukas, 1998), although a series of studies was reported recently (Scherer et al, 2003;Gerber et al, 2004a;Hendel et al, 2005;Michels et al, 2005;Neuser et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Nonexclusive mechanisms by which experience with chemical deterrents have been suggested to influence herbivores are: (1) a reduction in the herbivores' chemosensory sensitivity to the deterrent with exposure (Schoonhoven, 1969;Blaney et al, 1986); (2) habituation or reduced sensitivity to the taste and odor of the deterrent chemicals (Jermy et al, 1982;Jermy, 1987;Bernays, 1995); (3) an 'induction of feeding preferences' such that the herbivores prefer host plants containing certain chemicals to the exclusion of other adequate host plants (Jermy, 1987;Szentesi & Jermy, 1989;Bernays & Chapman, 1994;Bernays, 1995;del Campo et al, 2001) or (4) conditioning experience may involve forms of associative learning in the herbivores (Papaj & Rausher, 1983;Papaj & Prokopy, 1989). Tully et al (1994) demonstrated associative learning in response to aversive stimuli in larval Drosophila that persisted into adulthood. Reduced sensitivity, habituation, and induced preferences are unlikely in the wasp predators.…”
Section: Discussionmentioning
confidence: 99%